2010
DOI: 10.1007/s10764-010-9405-7
|View full text |Cite
|
Sign up to set email alerts
|

Life History of Cercopithecus mitis stuhlmanni in the Kakamega Forest, Kenya

Abstract: Comparative data from wild populations are necessary to understand the evolution of primate life history strategies. We present demographic data from a 29-yr longitudinal study of 8 groups of individually recognized wild blue monkeys (Cercopithecus mitis stuhlmanni). We provide estimates of life history variables and a life table for females. Most females had their first infant at 7 yr. The mean interbirth interval was 28 mo, and decreased from 31 to 18 mo if the first infant died within a year. Interbirth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 60 publications
1
52
0
Order By: Relevance
“…1 yr. Shortened interbirth intervals after the deaths of infants, through infanticide or other causes, have also been found in captive gray-cheeked mangabeys (Deputte 1991) as well as in several other primate species, including Sanje mangabeys (Cercocebus sanjei: Fernandez et al 2014) and captive golden-bellied mangabeys (C. agilis: Walker et al 2004), Hanuman langurs (Borries and Koening 2000), chacma baboons (Cheney et al 2004), and blue monkeys (Cercopithecus mitis: Cords and Chowdhury 2010;Cords and Fuller 2010). This suggests that infanticide could be an effective reproductive strategy for the male gray-cheeked mangabeys of Kibale and may in part explain aggression toward infants by immigrant males (Arlet et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…1 yr. Shortened interbirth intervals after the deaths of infants, through infanticide or other causes, have also been found in captive gray-cheeked mangabeys (Deputte 1991) as well as in several other primate species, including Sanje mangabeys (Cercocebus sanjei: Fernandez et al 2014) and captive golden-bellied mangabeys (C. agilis: Walker et al 2004), Hanuman langurs (Borries and Koening 2000), chacma baboons (Cheney et al 2004), and blue monkeys (Cercopithecus mitis: Cords and Chowdhury 2010;Cords and Fuller 2010). This suggests that infanticide could be an effective reproductive strategy for the male gray-cheeked mangabeys of Kibale and may in part explain aggression toward infants by immigrant males (Arlet et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Females in this population give birth primarily between January and March [18], a period that overlaps with a seasonal peak in fruit availability (January/February; Cords, unpublished data). A study on infant development in this population showed that infants markedly decrease daytime suckling and contact time with the mother after the third month of life, and move about largely independently by the age of six months [67].…”
Section: Methodsmentioning
confidence: 99%
“…Rain falls seasonally, with the dry season typically spanning December to March, and a shorter period of low rainfall in June/July [66]. Several groups of blue monkeys have been observed since 1979 [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations